Causal relationship between financial capital financial flows and economic growth in South Africa - Dyushu, Mphumleli (Graduate School of Business (GSB), 2025)
The study's main objective was to test the causal relationship between financial capital flows and economic growth in South Africa. Developing countries rely significantly on foreign capital inflows to supplement domestic savings for investment and growth. Foreign investment is essential to emerging nations' economic growth because it augments domestic savings for expansion and investment. Using a global financial capital pool has significant potential benefits for many developing nations. Due to low growth levels in emerging markets, efforts have been made to identify the factors that hinder growth. Capital flow movements has been one of those factors. There has been sharp reversal of portfolio flows, triggering concerns about financial stability and consequently, economic growth. South Africa's economy is heavily influenced by external financial flows, including foreign direct investment and portfolio investments. Policymakers need empirical evidence to formulate effective strategies that attract sustainable capital inflows while promoting economic growth and development. The study used secondary quantitative data from the World Bank, StatsSA and the South African Reserve Bank. Time series data that spanned from 1990 to 2023 was used for estimation. The study employed stationarity tests, cointegration analysis and the ARDL technique. The empirical results show that the relationship between Capital flows and GDP is negative. The relationship is marginal though and this suggests that capital flows, to a lesser extent, negatively affects GDP. The empirical results also reveals that the relationship between Terms of Trade and GDP in positive. The study recommended that there is need for government to come up with measures that can make capital flows contribute positively to growth. One measure would be to prolong the duration with which capital flows stay in S.A. in periods of economic uncertainty, capital tend to flow out of South African and this hurts growth.